The evaluation of heterocyclic amine formation in chemical model systems - Dennis, Cara L. (Kansas State University, 2014)
Heterocyclic amines (HCAs) are potentially carcinogenic and highly mutagenic byproducts of the Maillard browning reaction that form specifically in high temperature cooked meat products. Consumption of HCAs has been associated with various cancers including prostate, breast, colon, and pancreatic cancers and efforts have been made to understand formation and inhibition of these compounds. Chemical model systems are a preferred method to study the in vitro formation and inhibition of HCAs as the complex matrix effects found in meat are eliminated. Two black pepper extracts were evaluated for their efficacy on PhIP formation in model systems, but no significant results were observed. Secondly, four Maillard reaction variables were evaluated for their effect on formation of five HCAs (IQ, IQx, MeIQ, MeIQx, and 4,8-DiMeIQx) in chemical model systems with an effort to define an ideal model system. Precursor molar concentration (0.2/0.2, 0.4/0.4, 0.6/0.6, and 0.8/0.8 mmol), water percentage (0, 5, 10, and 15%), sugar type (fructose, galactose, glucose, and lactose), and sugar molar amount (quarter, half, equi, and double molar) were the four Maillard variables examined in the study. Additionally, four antioxidants (butylated hydroxyanisole (BHA), epigallocatechin gallate (EGCG), rosmarinic acid, and naringenin) were evaluated for their effect on HCA formation in chemical model systems. All four Maillard variables had a significant effect (p < 0.05) on the formation of HCAs in the model system, with an interaction effect occurring between water percentage and precursor concentration. The four antioxidants had no effect on the formation of HCAs in the model system. A model system containing 0.6/0.6/1.2 mmol of threonine, creatinine, and glucose, with 15% water was determined to be the best representative chemical model system for the formation of HCAs commonly formed in meats.
Keywords: Heterocyclic amines; Model systems; Maillard reaction; Food Science (0359)